If a+b=m , express a-b in terms of m . a-b=f(m)=?

idontknow Dec 2015 972 128 Earth Jan 10, 2020 #1 If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=\)? Reactions: greg1313

If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=\)?

P phillip1882 May 2013 94 10 Jan 10, 2020 #2 so lets take some examples and see if we can figure out a rule. 2+3 = 5 2-3 = -1 4+2 = 6 4 -2 = 2 7 +11 = 18 7 - 11 = -4 so it looks like our rule is: if a +b = m a -b = m -2b Reactions: topsquark and idontknow

so lets take some examples and see if we can figure out a rule. 2+3 = 5 2-3 = -1 4+2 = 6 4 -2 = 2 7 +11 = 18 7 - 11 = -4 so it looks like our rule is: if a +b = m a -b = m -2b

M mathman Forum Staff May 2007 6,909 762 Jan 10, 2020 #3 idontknow said: If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=? \) Click to expand... Doubtful. Example: m=0, then a+b=0. As a result let a=x thus b=-x so a-b=2x, where x can be any number. So f(m)=2x, not at all defined. Reactions: idontknow

idontknow said: If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=? \) Click to expand... Doubtful. Example: m=0, then a+b=0. As a result let a=x thus b=-x so a-b=2x, where x can be any number. So f(m)=2x, not at all defined.

topsquark Math Team May 2013 2,442 1,012 The Astral plane Jan 16, 2020 #4 idontknow said: If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=\)? Click to expand... Or, in symbols: a + b = m a - b = a + (b - 2b) = (a + b) - 2b = m - 2b -Dan Reactions: idontknow

idontknow said: If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms of m . \(\displaystyle a-b=f(m)=\)? Click to expand... Or, in symbols: a + b = m a - b = a + (b - 2b) = (a + b) - 2b = m - 2b -Dan